(untitled) (Nigerian Journal of Technology, 2016)
irrespective of their location. The traditional macro-only network have been proved ineffective when communication signal is required for users located in the cell edge and a certain distance away from the macrocell base station. This is because of excess attenuation of the signal due to fading and shadowing. Multipath fading and shadowing are major causes of performance degradation in mobile communication systems. This phenomenon which arises as a result of propagation effects (like scattering, diffraction and reflection), renders the traditional macro-only network communication with users far away from the macrocell base station and located in the cell edge less effective. The deployment of femtocells around the cell edge of this macrocell helps to reduce the effect of fading and shadowing thereby increasing the overall efficiency of the cellular network. Numerical simulation carried out for the macro-femto heterogeneous network using MATLAB shows how the effect of fading and shadowing was reduced. This holds a great promise for adaptive space-based wireless sensor networks, formation-flying satellites and constellations. http://dx.doi.org/10.4314/njt.v35i2.24